Phosphorylation of the Retinal Ribbon Synapse Specific t-SNARE Protein Syntaxin3B Is Regulated by Light via a Ca2 +-Dependent Pathway - Campbell, Joseph R.; Li, Hongyan; Wang, Yanzhao; Kozhemyakin, Maxim; Hunt, Albert J.; Liu, Xiaoqin; Janz, Roger; Heidelberger, Ruth (Frontiers in Cellular Neuroscience, 2020)
Neurotransmitter release at retinal ribbon-style synapses utilizes a specialized t-SNARE protein called syntaxin3B (STX3B). In contrast to other syntaxins, STX3 proteins can be phosphorylated in vitro at T14 by Ca2+/calmodulin-dependent protein kinase II (CaMKII). This modification has the potential to modulate SNARE complex formation required for neurotransmitter release in an activity-dependent manner. To determine the extent to which T14 phosphorylation occurs in vivo in the mammalian retina and characterize the pathway responsible for the in vivo phosphorylation of T14, we utilized quantitative immunofluorescence to measure the levels of STX3 and STX3 phosphorylated at T14 (pSTX3) in the synaptic terminals of mouse retinal photoreceptors and rod bipolar cells. Results demonstrate that STX3B phosphorylation at T14 is light-regulated and dependent upon the elevation of intraterminal Ca2+. In rod photoreceptor terminals, the ratio of pSTX3 to STX3 was significantly higher in dark-adapted mice, when rods are active, than in light-exposed mice. By contrast, in rod bipolar cell terminals, the ratio of pSTX3 to STX3 was higher in light-exposed mice, when these terminals are active, than in dark-adapted mice. These results were recapitulated in the isolated eyecup preparation, but only when Ca2+ was included in the external medium. In the absence of external Ca2+, pSTX3 levels remained low regardless of light/dark exposure. Using the isolated rod bipolar cell preparation, we next showed that elevation of intraterminal Ca2+ alone was sufficient to increase STX3 phosphorylation at T14. Furthermore, both the non-specific kinase inhibitor staurosporine and the selective CaMKII inhibitor AIP inhibited the Ca2+-dependent increase in the pSTX3/STX3 ratio in isolated rod bipolar cell terminals, while in parallel experiments, AIP suppressed rod bipolar cell depolarization-evoked exocytosis, measured using membrane capacitance measurements. Our data support a novel, illumination-regulated modulation of retinal ribbon-style synapse function in which activity-dependent Ca2+ entry drives the phosphorylation of STX3B at T14 by CaMKII, which in turn, modulates the ability to form SNARE complexes required for exocytosis.